2016
DOI: 10.3892/ol.2016.5341
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Thy1 and ITGA6 is associated with invasion, metastasis and poor prognosis in human gallbladder carcinoma

Abstract: Gallbladder cancer (GBC) is a rare but highly aggressive cancer for which no well-accepted prognostic biomarkers have been identified. Thymus cell antigen 1 (Thy1), also known as cluster of differentiation (CD)90, and integrin α6 (ITGA6), also known as CD49f, are important molecules in cancer and putative markers of various stem cell types. However, their role in GBC remains to be elucidated. In the present study, Thy1 and ITGA6 expression status in clinical GBC samples, which comprised squamous cell/adenosqua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 45 publications
2
35
0
Order By: Relevance
“…For instance, miR‐429 was found down‐regulated in primary OS lesion and OS cell lines , miR‐3928 was down‐regulated in OS tissues and miR‐199a‐3p was expressed low in human OS cells . Further, according to previous studies, lower expression level of miR‐127‐3p was also found in OS , glioblastoma , and epithelial ovarian carcinoma , whereas ITGA6 was proved highly expressed in leukemia and gallbladder carcinoma .…”
Section: Discussionmentioning
confidence: 80%
“…For instance, miR‐429 was found down‐regulated in primary OS lesion and OS cell lines , miR‐3928 was down‐regulated in OS tissues and miR‐199a‐3p was expressed low in human OS cells . Further, according to previous studies, lower expression level of miR‐127‐3p was also found in OS , glioblastoma , and epithelial ovarian carcinoma , whereas ITGA6 was proved highly expressed in leukemia and gallbladder carcinoma .…”
Section: Discussionmentioning
confidence: 80%
“…ITGA6 has been demonstrated to be dramatically downregulated and to act as an oncogene in various cancers. For example, Zhang et al found that overexpression of ITGA6 was associated with invasion, metastasis, and poor prognosis in human gallbladder carcinoma . Brooks et al found that ITGA6 was directly regulated by hypoxia‐inducible factors and enriched for cancer stem cell activity and invasion in metastatic breast cancer models .…”
Section: Discussionmentioning
confidence: 99%
“…The densely connected hub proteins are more likely to be essential proteins, which is referred to as the "centrality-lethality rule" [47]. THY1 is a glycophosphatidylinositol-anchored protein, which has been proposed to play important roles in cancers [48]. Function analysis showed that THY1 was signi cantly enriched in function associated with positive regulation of GTPase activity.…”
Section: Discussionmentioning
confidence: 99%